Electoral Behavior in Unreformed England : Plumpers, Splitters, and Straights - Phillips, John A. (Book collections on Project MUSE., 2014)
This work examines the development of popular politics in four representative English towns between 1761 and 1802. The book addresses hitherto unanswered yet fundamental questions about the electorate and the electoral system of later eighteenth-century England. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting t.